Comparison of a distance runner to a sprinter - Forrester, N.; Hill, G.
Although the execution of running may be very simple for some, the complexity involved can be witnessed in the difference of running styles of each runner. We set out to examine if there existed a difference in the foot strike pattern of sprinters and distance runners. If there was a difference we wanted to know if it was possible for a shoe (AirMax) to fit the needs of both runners. As thought, we did find a difference. Just from the stick diagrams we saw that there was a dorsiflexion in the distance runner (indicating that there was heel strike), and in the sprinter dorsiflexion was absent. From our analysis, we found that the distance runner occupied 5s of cycle time and the sprinter occupied 3s, in the stance phase. However, during the stance phase the distance runner was plantarflexed for only 78% of the time, while the sprinter was always plantarflexed. Hence, the frontal portion of the foot spent a longer period in contact with the ground, for the sprinter. This is important, because according to Perry (1995), the second metatarsal experiences the greatest pressure during walking in running shoes. If less time is spent on the metatarsals, then the distance runner is not subject to the same amount of pressure as would be the sprinter. In addition, the sprinter had a larger degree of plantarflexion in the stance phase. This means that a greater region of the foot was in contact with the ground, and not just the metatarsals. As Lavery notes, the site of highest barefoot pressure was the great-toe. With the sprinter having a greater plantarflexion, it is probable that the great-toe experienced more pressure than the distance runner. Since the distance runner does not plantarflex as much in the stance phase (as the sprinter), the great-toe may not have made contact with the ground. Finally, for the distance runner, the heel strike distributes the pressure applied throughout the foot. However, for the distance runner, that pressure remains isolated to the frontal portion of the foot. With these different results from the sprinter and distance runner, the shoes required for each runner must meet different needs. For the distance runner, the shoe would need to withstand more pressure applied in the heel region. For the sprinter, the shoe needs to withstand the pressure applied in the forefoot area.